Evaluation of Electronic Resources Utilization and Users Satisfaction at Kabale University Library. - Muhanguzi, Shadrach (Kabale University, 2023)
The purpose of this study was to evaluate the utilization of electronic resources and users’ satisfaction at the Kabale University Library. It was guided by four specific objectives: determining the extent of electronic resource utilization at the Kabale University library, finding out the relevance of electronic resource utilization, identifying the challenges limiting the utilization of electronic resources, and suggesting possible solutions to the challenges limiting the utilization of electronic resources at Kabale University. The study was conducted from January 2022 to December 2022. The study used a descriptive research design utilizing both qualitative and quantitative data collection and analysis approaches. Using purposive sampling techniques, a total of 75 lecturers were selected to participate in the study. Data was collected using questionnaires and key informant interviews. Majority of the participants on the extent of electronic resource utilization by the library at Kabale University strongly agreed that they use the library to get internet services. It was found that the majority of participants strongly agreed with academic/research purpose as one of the relevance of electronic resources utilization by the library users. The study concluded that poor information technology infrastructure development affects electronic resource utilization. It was also concluded that majority of the participants strongly agreed that there is need for a library consortium to enhance electronic resources.